Weakly Relative Poverty - Chen, Shaohua; Ravallion, Martin (2012)
Prevailing measures of relative poverty put an implausibly high weight on relative deprivation, such that measured poverty does not fall when all incomes grow at the same rate. This stems from the (implicit) assumption in past measures that very poor people incur a negligible cost of social inclusion. That assumption is inconsistent with evidence on the social roles of certain private expenditures in poor settings and with data on national poverty lines. The authors propose a new schedule of "weakly relative" lines that relax this assumption and estimate the implied poverty measures for 116 developing countries. The authors find that there is more relative poverty than past estimates have suggested. In 2005, one half of the population of the developing world lived in relative poverty, half of whom were absolutely poor. The total number of relatively poor rose over 1981-2005, despite falling numbers of absolutely poor. With sustained economic growth, the incidence of relative poverty becomes less responsive to further growth. Slower progress against relative poverty can thus be seen as the "other side of the coin" to success against absolute poverty.